2001
DOI: 10.1536/jhj.42.295
|View full text |Cite
|
Sign up to set email alerts
|

Age and Sex Differences in the P-Wave Signal-Averaged Electrocardiogram in a Japanese Study Population.

Abstract: SUMMARYNormal P wave signal-averaged electrocardiogram (SAE) values were determined in 120 healthy Japanese adults (56 men, 64 women), aged 44.5±10.2 years (mean±SD). The P wave trigger method was used with a Fukuda FDX6500 recorder. We used bipolar Weak positive correlations were observed between fPd (F) and body surface area, fPd (F) and age, fPd (B) and body surface area, fPd (B) and age, fPd (C) and body surface area, and fPd (C) and age. There was no evident correlation, however, between either forward or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
1
2
Order By: Relevance
“…4,20,21 However, signalaveraged P waves in healthy individuals are less well described. 24 In this study, we do not observe any significant changes in P-wave variables between BL and FU. Ishimoto and coworkers reported a PWD of 121 ± 9 ms in a normal control group.…”
Section: The Normal P Wave and Its Evolution-temporal Variablescontrasting
confidence: 48%
See 1 more Smart Citation
“…4,20,21 However, signalaveraged P waves in healthy individuals are less well described. 24 In this study, we do not observe any significant changes in P-wave variables between BL and FU. Ishimoto and coworkers reported a PWD of 121 ± 9 ms in a normal control group.…”
Section: The Normal P Wave and Its Evolution-temporal Variablescontrasting
confidence: 48%
“…23 These data were suggested to confirm the presence of age-related conduction disturbances but the lack of age-related Pwave prolongation has also been reported. 24 In this study, we do not observe any significant changes in P-wave variables between BL and FU. Possibly a 3-year follow-up period is too short for statistically significant age-related changes such as PWD prolongation to occur.…”
Section: The Normal P Wave and Its Evolution-temporal Variablescontrasting
confidence: 48%
“…Previous studies have reported that the FPD correlates with LAD, age, and history of hypertension. [11][12][13][14][15] It has been reported that the initial potentials correlate with indices of electrophysiologic measurements, although the statistical significance is weak. 16) In the present study, we demonstrated that the FPD correlates positively with interatrial conduction time, which is one of the electrophysiologic indices for atrial conduction abnormalities.…”
Section: Discussionmentioning
confidence: 99%